2010
DOI: 10.1097/jto.0b013e3181ce684f
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Class III Beta-Tubulin Correlates with Unfavorable Survival Outcome in Patients with Resected Non-small Cell Lung Cancer

Abstract: TUBB3 expression is an independent unfavorable prognostic marker in patients with curatively resected non-small cell lung cancer who did not receive adjuvant chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
2
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 31 publications
0
38
2
1
Order By: Relevance
“…TUBB3 has been investigated to determine the role of this gene in resistance to paclitaxel and docetaxel. TUBB3 is also an independent prognostic marker in patients with resected NSCLC that have not received chemotherapy (38)(39)(40). In the present study, the expression of RRM1 andTUBB3 was not associated with the DFS time of patients with NSCLC that received adjuvant cisplatin-based chemotherapy.…”
Section: Discussioncontrasting
confidence: 42%
“…TUBB3 has been investigated to determine the role of this gene in resistance to paclitaxel and docetaxel. TUBB3 is also an independent prognostic marker in patients with resected NSCLC that have not received chemotherapy (38)(39)(40). In the present study, the expression of RRM1 andTUBB3 was not associated with the DFS time of patients with NSCLC that received adjuvant cisplatin-based chemotherapy.…”
Section: Discussioncontrasting
confidence: 42%
“…After reading the title and abstract, 61 articles were selected to read the full articles by two investigators (ZX Zhang, XD Yin), 3 of them were excluded as the cohort was similar in other articles (studies excluded [9], [10], [11]; studies included [12], [13], [14]. Finally, 22 studies were found eligible for the systematic review which were published between 2007 and 2014 [15], [13], [16][24], [12], [25]–[32], [14], [33], in which 5 studies could not provide sufficient data for meta-analysis [16], [19], [20], [32], [14]. Figure 1 shows the flow chart of the search result.…”
Section: Resultsmentioning
confidence: 99%
“…11 studies compared the DFS between EGFR mutations and wild-type groups [18], [22], [12], [25], [26], [27], [28], [29], [30], [31], [33]. Significant heterogeneity was detected among the studies (I 2  = 62%, P  = 0.003).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, an individual or crowd capable of obtaining benefits most from chemotherapy is screened out by detecting biological indicators like genes and proteins, which is of great importance to realize NSCLC individualized treatment, improve individual therapeutic effects and decrease toxic and side effects. Detecting the expression levels of RRM1, ERCC1 and BRCA1 genes in tumor tissue to screen out the patients sensitive to capecitabine is a hot topic in the field of lung cancer at present (Lee et al, 2008;Koh et al, 2010;Hubner et al, 2011).…”
Section: Discussionmentioning
confidence: 99%